Metals Doped TiO2 Nanoparticle as an Efficient Photoelectrode in Dye-Sensitized Solar Cells: A Review - Asmaa Al-Baitai; Madeeha Mahmood; Saifaldeen abdulhussein; Saifaldeen Abdalhadi (Nanochemistry Research)
Dye synthesis solar cells (DSSCs) are one of the most promising third-generation solar cells due to their simple fabrication, low cost, and chemical versatility. Many factors directly affect the efficiency of DSSCs, and the photoanode plays an important role in improving efficiency through its ability to adsorb dye, electron injection, the ability of recombination, and electron transfer. Due to their wide band gap, stability, and ability to absorb dyes, metal oxide semiconductor nanoparticles such as ZnO and TiO2 are usually used as photoanodes in DSSCs. The working electrode can be improved by adding a low percentage of nano-semiconductors to the TiO2, such as nanometals or other metal oxide. In this review, we report the components of DSSCs and mention their principal work. Then, we discuss different techniques that use metal nanoparticles doped on TiO2 as a photoanode and examine the effect of this dopant on the efficiency of DSSCs.